ONLINE LEARNING ANALYSIS FROM THE PERSPECTIVE OF PRE-SERVICE BIOLOGY TEACHERS - Maesaroh Maesaroh (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Pembelajaran merupakan interaksi antara pendidik dan peserta didik dengan bantuan alat, media dan sumber belajar untuk mencapai tujuan belajar. Proses belajar umumnya terjadi secara tatap muka di ruangan kelas atau laboratorium. Pembelajaran daring telah dilaksanakan secara penuh selama semester genap tahun akademik 2020/2021 untuk mencegah penyebaran Covid-19. Penelitian ini menyajikan informasi berupa analisis pembelajran daring dari perspektif mahasiswa berupa proses pembelajaran, hambatan, kelebihan, serta peluang. Pembelajaran daring belum terlaksana dengan efektif dan efisien dari perspektif mahasiswa program studi Pendidikan biologi. Pembelajaran daring dinyatakan belum dapat dilaksanakan pada kegiatan praktikum dan pengembangan keterampilan kerja ilmiah. Pembelajaran terkendala pada kualitas infrastruktur, SDM, dan implementasi variasi strategi pembelajaran secara daring. Keunggulan pembelajaran daring menurut mahsiswa membantu menjadi pebelajar yang mandiri sehingga dapat mengenali kemampuan masing-masing dalam menguasi materi.Abstract: Learning is an interaction between educators and students with the help of tools, media and learning resources to achieve learning goals. In biology, he learning process generally occurs face-to-face in a classroom or laboratory. Online learning has been fully implemented during the even semester of the 2020/2021 academic year to prevent the spread of Covid-19. This study provides information in the form of online learning analysis from a student perspective in the form of learning processes, obstacles, strengths, and online learning opportunities. Online learning has not been carried out effectively and efficiently from the perspective of Biology Education study program students. Online learning is declared unable to be implemented in practicum activities and scientific work skills development. Learning is constrained by the quality of infrastructure, human resources, and the implementation of various online learning strategies. The advantages of online learning according to students are helping to become independent learners so they can recognize their respective abilities in mastering the material.